The future for diabetic foot ulcer prevention: A paradigm shift from stratified healthcare towards personalized medicine. (16th January 2020) - Van Netten, Jaap J.; Woodburn, James; Bus, Sicco A.
ABSTRACT: Prevention of diabetic foot ulcers is important to reduce the burden of diabetic foot disease. However, we found that ulcer prevention is underexposed in research and clinical practice. Barriers to explain this are seen in patient's goal‐setting; in the lack of interdisciplinary teams for ulcer prevention; in sample sizes and funding for research; in industrial engagement; and in limited understanding of ulcer development. Rather than separately solving these barriers, we propose a paradigm shift from stratified healthcare towards personalized medicine for diabetic foot disease. Personalized medicine aims to deliver the right treatment to the right patient at the right time, based on individual diagnostics. Different treatment strategies should be available for different patients, delivered in an integrated, objective, quantitative and evidence‐based approach. More than on the classical risk factors of peripheral neuropathy and peripheral artery disease, individual diagnostics should focus on modifiable risk factors for ulceration. This includes structured biomechanical and behavioral profiling, while new research with (big) data science may identify additional risk factors, such as geographical or temporal patterns in ulceration. Industry involvement can drive the development of wearable instruments and assessment tools, to facilitate large‐scale individual diagnostics. For a paradigm shift towards personalized medicine in prevention, large‐scale collaborations between stakeholders are needed. As each ulcer episode not prevented costs about €10, 000 in medical costs alone, such investments can be cost‐effective. We hope to see more discussions around this paradigm shift, and increasing investments of energy and money in diabetic foot ulcer prevention in research and clinical practice.